2016
DOI: 10.1002/2015ja022117
|View full text |Cite
|
Sign up to set email alerts
|

Influences of shear in the ion parallel drift velocity and of inhomogeneous perpendicular electric field on generation of oblique ion acoustic waves

Abstract: It is well known that the broadband electrostatic turbulence observed in the topside auroral ionosphere can be identified with electrostatic ion cyclotron and/or oblique ion acoustic waves. Under certain conditions generation of the ion cyclotron modes is inhibited, so that the oblique ion acoustic waves become the prevailing part of the broadband noise. While generation of ion cyclotron waves by the inhomogeneous distribution of energy density (IEDD) instability has been actively studied in recent years, much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…26 and 27, and references herein). Numerical stability analysis using FAST or FREJA satellite data was carried out in recent papers, 20,21,[28][29][30] and it was confirmed that the IEDD instability could play an important role in the creation of electrostatic broadband turbulence (or noise) in the auroral zone and explain the experimental observations.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…26 and 27, and references herein). Numerical stability analysis using FAST or FREJA satellite data was carried out in recent papers, 20,21,[28][29][30] and it was confirmed that the IEDD instability could play an important role in the creation of electrostatic broadband turbulence (or noise) in the auroral zone and explain the experimental observations.…”
Section: Introductionmentioning
confidence: 74%
“…17,[19][20][21]. It was shown that inhomogeneous structures of electric field and field-aligned current produce broadband spectra for several wave modes such as EIC 21 and IA 30 waves. The role of the IEDD instability could also be broader than the production of broadband waves in the auroral zone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations